PENERAPAN TERAPI PROGRESSIVE MUSCLE RELAXATION TERHADAP NYERI AKUT PRE OPERASI FRACTURE NECK FEMUR - Hirdes Harlan Yuanto; Ahmad Rosuli; Masroni Masroni; Silvia Ayu Yulia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Fractures or breaks in the continuity of bone structure are a major problem in the health sector. Tissue damage causes several typical clinical manifestations, namely pain. If not treated immediately, it can cause immobilization of the individual to carry out self-care activities. This study aims to determine the application of progressive muscle relaxation therapy to acute pain in preoperative patients with left femoral neck fractures in the Agung Wilis Accident Surgery Room, Blambangan Hospital. The research design used a case study of nursing care for femoral neck fracture patients with acute pain and carried out assessment, diagnosis, action planning, implementation and evaluation. Data collection methods through interviews and direct observation. The results of Mrs. N complained of pain from a femoral neck fracture, pain like being stabbed in the thigh area radiating to the pelvis on a scale of 7, the pain seemed to come and go. Interventions are given to reduce pain levels with progressive muscle relaxation. The evaluation revealed a change in the scale before therapy was given, namely a pain scale of 7 to 5. It can be concluded that the application of progressive muscle relaxation can be an alternative in treating pain in fracture sufferers.